Factors Associated with Physical Fitness among Overweight and Non-Overweight Austrian Secondary School Students - Gerhard Ruedl (International Journal of Environmental Research and Public Health, 2019)
The aim of the study was to evaluate factors associated with physical fitness (PF) among overweight and non-overweight Austrian secondary school students. PF was measured using the German motor test (DMT) 6−18 and students were asked about sex, migration background, weekly leisure time physical activity and daily electronic media use. In total 560 adolescents (56.6% female) with a mean age of 15.4 ± 1.4 years and a mean body mass index (BMI) of 22.5 ± 4.2 kg/m² were evaluated with 130 (23.2%) students classified as overweight or obese. For the total cohort, results of the multiple linear regression analysis (R2 = 0.34) revealed that a younger age (β = −0.16), no migration background (β = 0.13), a lower BMI (β = −0.29), a higher weekly leisure time physical activity (β = 0.34) and a lower daily electronic media use (β = −0.15) were associated with increased PF. Separate regression analyses for non-overweight and overweight students showed similar regression coefficients except for BMI. In conclusion, the positive influence of modifiable factors such as lower BMI, higher self-reported weekly leisure time sports activity and lower self-reported daily electronic media use should be considered already at young ages to increase physical fitness in overweight and non-overweight youth.